2006
DOI: 10.1161/circulationaha.105.581405
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Soluble Guanylate Cyclase Reverses Experimental Pulmonary Hypertension and Vascular Remodeling

Abstract: Background-Severe pulmonary hypertension is a disabling disease with high mortality, characterized by pulmonary vascular remodeling and right heart hypertrophy. Using wild-type and homozygous endothelial nitric oxide synthase (NOS3 Ϫ/Ϫ ) knockout mice with pulmonary hypertension induced by chronic hypoxia and rats with monocrotalineinduced pulmonary hypertension, we examined whether the soluble guanylate cyclase (sGC) stimulator Bay41-2272 or the sGC activator Bay58-2667 could reverse pulmonary vascular remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
148
1
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(167 citation statements)
references
References 44 publications
8
148
1
10
Order By: Relevance
“…Therefore, pharmacological stimulation of sGC is an appealing strategy to treat PAH and discovery of pharmacological tools, such as sGC stimulators, is of high interest. Recently, the sGC stimulator BAY 41-2272 was shown to be a systemic and pulmonary vasodilator [11] and to improve PAH in experimental models of PAH [12]. The aim of the present study was to investigate the expression of sGC in IPAH and experimental models of PAH.…”
mentioning
confidence: 94%
“…Therefore, pharmacological stimulation of sGC is an appealing strategy to treat PAH and discovery of pharmacological tools, such as sGC stimulators, is of high interest. Recently, the sGC stimulator BAY 41-2272 was shown to be a systemic and pulmonary vasodilator [11] and to improve PAH in experimental models of PAH [12]. The aim of the present study was to investigate the expression of sGC in IPAH and experimental models of PAH.…”
mentioning
confidence: 94%
“…137 In animal models of PH, sGC expression was similarly upregulated, and direct sGC activation improved hemodynamics and vascular remodeling. [137][138][139] A proof-of-concept study was conducted that included 19 adult patients with PH (either PAH or chronic thromboembolic PH) who received the new drug riociguat (BAY 63-251). 140,141 That study suggested that riociguat was safe and found that pulmonary hemodynamics and cardiac output improved in a dose-dependent fashion.…”
Section: Nitric Oxide-cgmp Cascade: Inhaled Nitric Oxidementioning
confidence: 99%
“…These pulmonary vasodilators have been investigated in experimental models of pulmonary arterial hypertension (PAH) (3), pressure and hypoxia induced myocardial injury, ischemia-reperfusion injury of the lung (4), and in patients with PAH (5,6) or decompensated heart failure (7). Pulmonary vasodilators have been shown to reduce pulmonary vascular resistance (PVR) and improve remodelling following myocardial injury (8,9).…”
Section: Introductionmentioning
confidence: 99%